Search 70,368 tutors

# 5r-7(1+r)=5

5r-7(1+r)=5

First solve for the -7(1+r) = -7-7r,    then plug back into equation -

5r-7-7r= 5

5r-7r = 5+ 7 (when -7 goes over to the other side, the - sign changes to +)

-2r=12

r=-6

To check -

5r-7(1+r) , where r = -6

5(-6) -7(1+(-6))

-30 -7(-5) ---> multiply first

-30 +35 = 5

Therefore, r = -6

thank u soooo much i wasnt exactly sure on wat operation to do but u helped me sooo..... THX 12/5/2012

You very welcome. Here is  rule of thumb, I call it BODMAS

B = Brackets "()"

O = Off which denote "="

D = Division "/"

M = Multiply "x"

S = Subtract "-"

These must follow in order, in other words, for every equation, the bracket columns must be solved first or expanded. In your equation, solved the brackets first, then further down the order. Also, keep in mind of these

(-) *(-)  = +         (+)*(+) = +

(-)*(+)  = -          (+)*(-)= -

If you follow these simple rules, you'll be able to solve most algebraic equations easily.

12/5/2012

5r - 7 - 7r = 5

-2r - 7 = 5

-2r = 12

r = -6

where did u get -7r ? im confused can u plzz explain how u solved it 12/5/2012

by multiplying the -7 through the (1+r), so -7 x 1 = -7 and -7 x (r) = -7r

therefore -7(1+r) = -7-7r

12/5/2012

Further on in the problem... Remember that what you do to one side of the equation you must do to the other to keep them equal. So...

-2r - 7 + 7 = 5 + 7                  =>>         -2r = 12

See how we added 7 to both sides so that only the varialbles are on one side while the numbers are on the other side? This allows us to divide by the co-efficient ( -2 in -2r) and get the resulting r = -6.

12/5/2012

`thx bigg help i got stuck cuz i 4got i had 2 use -7 instead of +7 wen u do the distributive property`

12/5/2012